Functional Analysis of PsAvr3c Effector Family From Phytophthora Provides Probes to Dissect SKRP Mediated Plant Susceptibility - Zhang, Ying; Huang, Jie; Ochola, Sylvans O.; Dong, Suomeng (Frontiers in Plant Science, 2018)
PsAvr3c is an effector identified from oomycete plant pathogen Phytophthora sojae that causes soybean root and stem rot disease. Earlier studies have demonstrated that PsAvr3c binds to a novel soybean spliceosomal complex protein, GmSKRP, to reprogram the splicing of hundreds of pre-mRNAs and consequently subvert host immunity. PsAvr3c family genes are present in some other Phytophthora species, but their function remains unknown. Here, we characterized the functions of PsAvh27b (PsAvr3c paralog from P. sojae), ProbiAvh89 and PparvAvh214 (orthologs from P. cinnamomi var. robiniae and Phytophthora parvispora, respectively). The study reveals that both PsAvh27b and ProbiAvh89 interact with GmSKRPs in vitro, and stabilize GmSKRP1 in vivo. However, PparvAvh214 cannot interact with GmSKRPs proteins. The qRT-PCR result illustrates that the alternative splicing of pre-mRNAs of several soybean defense-related genes are altered in PsAvh27b and ProbiAvh89 when over-expressed on soybean hairy roots. Moreover, PsAvr3c family members display differences in promoting Phytophthora infection in a SKRP-dependent manner. Overall, this study highlights that the effector-mediated host pre-mRNA alternative splicing occurs in other pathosystems, thus providing new probes to further dissect SKRP-mediated plant susceptibility.